Sistem Cash on Delivery (COD) dalam Jual Beli Online Menurut Perspektif Ekonomi Islam - Musbikhin, Musbikhin; Maghfur, Arif; Elisia, Dian (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Online buying and selling are transactions carried out by parties using the internet network. The payment method that is often used today is the COD system. The aim of this research is to find out and explain the mechanism of the Cash On Delivery (COD) system in online buying and selling according to an Islamic economic perspective. In this research the researcher used a library research method with descriptive qualitative analysis using a deductive method regarding the cash on delivery (COD) system and analyzed using an Islamic economics approach. The results of this research include the following: 1) the online buying and selling mechanism with the COD system in the marketplace can be implemented by selecting the goods first and then payment is made in cash when the goods arrive. To purchase products, you can order them via the website or application. 2) (2) Based on the analysis of online buying and selling using the COD system carried out by the marketplace, it is in accordance with Islamic economic principles, such as aspects of justice, transparency and compliance. So online buying and selling using the COD system is permitted from a Sharia Economic perspective.